Risk adjustment and risk-adjusted provider profiles. (30th September 2005) - Shwartz, Michael; Ash, Arlene; Pekoz, Erol
Provider profiles are an important component of efforts to improve both healthcare productivity and quality. Risk adjustment is the attempt to account for differences in the risk for specific outcomes of cases in different groups in order to facilitate more meaningful comparisons. The value of provider profiles, whether used internally or released to the public, depends both on adequate risk adjustment and on distinguishing systematic differences in either the quality or productivity of care from random fluctuations. In this paper, we discuss how risk adjustment systems can be used to predict outcomes for individual cases; methods for measuring and comparing the performance of risk adjustment systems; and how random variation can affect provider performance data and several approaches for addressing random variation in risk-adjusted provider profiles. In the last section, we illustrate the methods discussed by developing and analysing risk-adjusted provider profiles for 69 family practitioners responsible for over 68, 000 cases.